(untitled) (Malaysian Journal of Civil Engineering, 2018)
The liquid limit of clay treated with e lectrolytes were investigated and examinedwith respect to electrolyte types and concentration , time-dependent effects, andmineralogy Of clay. The findings indicated that the types and concentration ofele ctrolytes in the pore fluid of clay have a marked effect on the liquid limit ofclay. Ageing has a pronoun ced effect on the liquid limit, particularly for claytreated with cemen ting agents.